An access control model for data security sharing cross‐domain in consortium blockchain. Issue 1 (6th January 2023) - Liu, Yang; Yang, Weidong; Wang, Yanlin; Liu, Yang
Abstract: With the rapid increment of the demand for data sharing among parties, data is considered a cornerstone component to provide value in the big data environment. Concerns regarding sharing data security have impeded the development of cross‐domain data interaction. Therefore, an access control model for data security sharing cross‐domain is proposed, Fabric‐ABAC, that is based on Hyperledger Fabric and Attribute‐based Access Control (ABAC). In order to solve the data security challenges caused by a trusted central organization implementation, a distributed environment is constructed that consists of stakeholders among parties. The unified attribute model is designed for multi‐environment combined with smart contracts. Fabric‐ABAC realizes multi‐level, fine‐grained, and auditable access control, enabling data security through automatic permission verification. Considering the ledger is visible to all participants in consortium blockchain, it is necessary to protect the confidentiality of sensitive data. Thus, Proxy Re‐Encryption (PRE), which is implemented by smart contracts, is adopted in the scheme to realize the ciphertext interaction without the third party. The security of PRE and the access control model used in Fabric‐ABAC is discussed to show that a secure environment for data sharing is provided. Moreover, the completeness of the implementation and effectiveness of the system performance in the multi‐domain environment is demonstrated in the experimental results. Abstract : This paper proposed a cross‐domain access control model based on Hyperledger Fabric, which combines the Proxy Re‐Encryption algorithm and ABAC implemented by smart contracts, maintains the confidentiality of data in the ledger and provides a secure decentralized environment for data interaction. The experiments proved that our scheme can resist unauthorized attacks efficiently and ensure the confidentiality of shared resources, and it has superior performance.